Middle-run impacts of comprehensive early childhood interventions: Evidence from a pioneer program in Chile - Britta Rude (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
This paper analyzes the impact of comprehensive and universal early childhood development programs on outcomes in middle childhood. I exploit the birth eligibility cutoff of a pioneer intervention of this type in Chile and use administrative data on grade point averages, standardized test scores, and an extensive early childhood development survey. Program exposure raises standardized math scores by 1.8 percent of a standard deviation, standardized reading scores by 4.0 percent of a standard deviation and grade point averages by 0.03 percent of a standard deviation. However, the effect is less pronounced for girls and socioeconomically vulnerable children. Impacts on several other child development outcomes also differ by gender and socioeconomic status. A cost-benefit analysis suggests that targeted programs might be more cost-effective than comprehensive programs.
Keywords: I24; I28; I38; J13; J24; O15; 330; Education and inequality; government policy; children; human capital